9. Drop attacks in Lennox–Gastaut Syndrome: Is Rufinamide the answer? - Yakubov, Boris; Shaw, Janet; Embuido, Jose; Hwang, Paul (Clinical neurophysiology, 2016)
The purpose of this study is to determine whether Banzel (Rufinamide) improves the control of drop attacks in patients with Lennox–Gastaut Syndrome, and whether it controls other seizure types in LGS. There are 10 patients with Lennox–Gastaut Syndrome who were candidates for participating in the Rufinamide retrospective cohort-controlled study. Presently, four of five patients are prescribed the drug Rufinamide. They are compared with the control group of LGS 4/5 subjects not on Rufinamide. Rufinamide dosage was started at 100–400mg daily dose, while other anti-epileptic drugs (AEDs) were continued in the treated group. The control group continued on original AEDs without the addition of Rufinamide. The most common AEDs were Valproic acid, Clobazam, Lamotrigine, and Topiramate. After a minimal period of six months of Rufinamide, the treated group had fewer drop attacks than the control group. Approximately 80% of patients (4/5) responded positively to Rufinamide. The treated group was more alert by caregiver observation, and had less drug interactions with other AEDs. Overall an improved quality of life was found with the Rufinamide treatment, leading to continuation of the new drug past the study period. One patient dropped out from the study due to severe side effects to Rufinamide: (1/5 or 20%). Rufinamide at therapeutic doses reduced the frequency of drop attacks or tonic seizures more than other AEDs. There may also be some improvement in control of atypical absences and/or myoclonic seizures in LGS. A subjective presentation of compared quality of life care from Rufinamide for LGS needs to be confirmed in a larger controlled study by quantitative age – specific assessment.